2010
DOI: 10.1364/oe.18.009525
|View full text |Cite
|
Sign up to set email alerts
|

50 fs soliton compression of optical clock pulse recovered from NRZ data injected SOAFL

Abstract: Mode-locking of semiconductor optical amplifier fiber laser (SOAFL) with 50 fs pulses by extracting the clock of an optical non-return-to-zero (NRZ) data injection is demonstrated. The efficiency of mode-locking in the SOAFL is improved by increasing the seeding power of the large-duty-cycle NRZ data from 3 to 8 dBm into the SOA driven at biased current of 350 mA. After linear dispersion compensation, the mode-locked SOAFL pulsewidth can be further shortened from 20 to 3 ps by increasing the DCF length up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In our opinion, the physical mechanism underlying pulse formation in this system is the interaction between the counterpropagating pulses that is at work in colliding-pulse mode-locked lasers (see e.g., [17]), which is based on the ultrafast dynamics of the gain in active semiconductor systems as described in [18]. This same mechanism is, in our opinion, the one that leads to active ML by counterpropagating injection of external pulses, as, for example, in [9,10,19,20].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In our opinion, the physical mechanism underlying pulse formation in this system is the interaction between the counterpropagating pulses that is at work in colliding-pulse mode-locked lasers (see e.g., [17]), which is based on the ultrafast dynamics of the gain in active semiconductor systems as described in [18]. This same mechanism is, in our opinion, the one that leads to active ML by counterpropagating injection of external pulses, as, for example, in [9,10,19,20].…”
Section: Resultsmentioning
confidence: 93%
“…Active ML of SOA-based fiber lasers in unidirectional ring cavities has allowed researchers to obtain optical pulses with a duration of 15 ps [9], which can be further amplified and compressed down to 50 fs [10]. Exploiting nonlinear polarization rotation of the field in the SOA, passive ML has been achieved in different situations.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have carried out experiments to either compress the optical temporal width or suppress the supermode noise to improve the laser stability. These schemes include (1) adiabatic soliton compression techniques [3][4], (2) multiple-step compression based on self phase modulation in highly nonlinear fibers or semiconductor optical amplifiers (SOA) [5][6], (3) a comb-like profiled fiber (CPF) to emulate dispersion decreasing fiber [7][8], (4) saturable optical absorbers such as nonlinear optical loop mirror (NOLM) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, semiconductor optical amplifiers (SOAs) have been used as the gain medium in fiber lasers [10][11][12]. Compared with the rare-earth-doped fibers, SOAs have many practical advantages, such as compact size, higher optical nonlinearity, larger gain bandwidth, and direct gain modulation by controlling injection current.…”
mentioning
confidence: 99%
“…As a result, the energy in the upper state and the gains of SOAs are typically smaller than those of doped fibers, but the response of SOAs is much faster. Lin et al demonstrated the generation of a 50 fs pulse from a 1.55 μm SOA-incorporated fiber ring, which was operated under the optical injection-induced actively HML scheme [10]. Yang et al [11] demonstrated the generation of 800 fs optical pulses using a 1.55 μm SOA with the passive mode-locking technique of nonlinear polarization evolution.…”
mentioning
confidence: 99%